1989
DOI: 10.1007/bf00916817
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age, race, and gender on peripheral blood mononuclear-cell subsets in healthy nonsmokers

Abstract: To investigate the influence of age, race, and gender on the cellular immune system, we determined T-cell, B-cell, monocyte, natural killer (NK)-cell, and HLA-DR+-cell subsets in 266 nonsmokers from a population-based random sample of healthy adults using monoclonal antibodies and flow cytometry. Blacks had a lower total white blood-cell count than whites (P less than or equal to 0.0001), due primarily to a decrease in granulocytes. There was no significant difference in absolute lymphocyte count between black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
89
4
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(120 citation statements)
references
References 26 publications
23
89
4
1
Order By: Relevance
“…In human, female had a higher frequency of CD4 + T cells but no significant gender effects were observed for CD14 + cells (18) and it was also found that the Indian adult females had significantly higher CD4 + T cell counts (28). It was the same with Chinese females who had a higher CD4 + /CD8 + T cell ratio than the males (29).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In human, female had a higher frequency of CD4 + T cells but no significant gender effects were observed for CD14 + cells (18) and it was also found that the Indian adult females had significantly higher CD4 + T cell counts (28). It was the same with Chinese females who had a higher CD4 + /CD8 + T cell ratio than the males (29).…”
Section: Discussionmentioning
confidence: 85%
“…There are conflictive reports about monocytes and DCs with age. Tollerud et al (18) investigated 266 nonsmokers and found no significant age effects were observed for CD14 + cells, but Della Bella et al (19) showed an increase of circulating monocytes with age. As DC subsets, mDCs and pDCs always have been studied together.…”
Section: Discussionmentioning
confidence: 97%
“…36 A gender-based difference in lymphocyte subsets have also been shown. Tollerud et al 38 examined 266 nonsmoking adults and found that women had a significantly higher proportion of CD4 + (helper T lymphocytes) cells and a lower proportion of CD8 + (suppressor T lymphocytes) than men. A similar tendency was observed in our 12 subjects.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Several investigators have studied whether the reference ranges used for most adults are applicable for the aged (22)(23)(24)(25)(26). As with the pediatric specimens, the evaluation of geriatric normals has been complicated by the methods of stratification, statistical analyses, and cytometry used in each study.…”
Section: Peripheral Bloodmentioning
confidence: 99%